2021
DOI: 10.1158/1078-0432.ccr-20-4521
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of IFN-Mediated Responses and Tumor Immunogenicity in Patients with Cervical Cancer Receiving Concurrent Chemoradiotherapy

Abstract: Purpose: To ask whether the expression of immune markers and IFN signaling in tumor biopsies changes during concurrent chemoradiotherapy (CCRT). Experimental Design: Tumor biopsies and peripheral mononuclear blood cells (PMBC) before and immediately after 20 Gy/10 fractions (F) of radiation treatment (RT) from 30 patients with cervical cancer receiving CCRT were evaluated by IHC and qRT-PCR for immune markers and correlated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Immune checkpoint expression often changes following therapy 8 , 26 28 . To determine whether chemotherapy alters the expression of CD47, we performed immunohistochemistry (IHC) analysis to assess CD47 protein levels in paired specimens from 81 osteosarcoma patients before and after chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Immune checkpoint expression often changes following therapy 8 , 26 28 . To determine whether chemotherapy alters the expression of CD47, we performed immunohistochemistry (IHC) analysis to assess CD47 protein levels in paired specimens from 81 osteosarcoma patients before and after chemotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…It is well-documented that RCT suppresses tumor growth and modulates anti-tumor immunity in various cancers. 6 , 7 In patients with CC, studies of bulk RNA-sequencing of immune cells have shown that RCT stimulates the expression of the co-stimulatory molecule CD28 8 and downregulates the expression of inhibitory molecules PD-1/PD-L1. 9 At the same time, multispectral flow cytometry of cervical smears revealed an early decrease in the number of T cells in the RCT-treated cervical TME, followed by an increase in their number at a later stage.…”
Section: Introductionmentioning
confidence: 99%
“…As such, investigations into radioimmunotherapy‐induced tumor ecosystem evolution are essential for guiding improvements in treatment strategies that achieve better long‐term disease control. To date, several studies have investigated radiochemotherapy‐induced tumor ecosystem evolution using bulk RNA‐sequencing and immune staining [ 7 , 8 ]. However, these findings were limited owing to the cellular heterogeneity in cancers.…”
mentioning
confidence: 99%